Determination of bending radii based on study of deformed state in places of formation of bending radii of bent prooﬁles (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
In this work, on the basis of the general expression for determining the polar radius r of an arbitrary material point under pure bending in the polar coordinate system, and using the basic provisions of the mechanics of a solid deformable medium, we determined the dependencies describing the components of the strain tensor in its cell. The components of the metal deformation tensor during profiling of a channel 150 × 100 × 2 mm were calculated for points located at the intersection of the axis of symmetry of the bending point and the boundary surfaces of the strip. It is established that, as a first approximation, it can be assumed that the deformed state of the bend during profiling is determined by the tangential and radial deformations, and the other components are equal to zero.
Keywords: curved profile; equal-shelf channel; deformed state; polar coordinate system; mechanics of a continuous deformable medium; minimum bending radius